North America - Koponen, Libby (New York : Children's Press, 2009)
Provides facts about North America, highlighting some of the continent's amazing natural features, plants, animals, and peoples, and including photographs, maps, and a time line.
Includes bibliographical references (p. 44-45) and index.
5.5
3-6
Keywords: North America -- Juvenile literature; North America; North America